A Building Ostracon from Deir el-Bahari - Barwik, Mirosław (Zeitschrift für ägyptische Sprache und Altertumskunde, 2009)
Ostracon inv. no. F.7077 was found in the 1960s in the area of the Thutmosis III temple at Deir el-Bahari, and a missing fragment in the season 1986/87 on the dumps between the Chapel of Hathor and the temple of Mentuhotep II Nebhepetre. An analysis of the text enables us to draw the conclusion that it is connected with an opening stage of work on the temple of Thutmosis III, possibly with the excavation of the temple platform hewn out in the bedrock to the south of the Hatshepsut temple. If such is the case, then the beginning of work on the Thutmosis III temple started about regnal year 43, documented by the present ostracon, which is the earliest of the series of documents dealing with the temple project. A change of the name of the temple (from Djeser-menu into Djeser-achet) took place some time between year 43 (II peret) and year 45 (IV peret), when work on the temple platform and pavement was nearly completed.